Demonstrations of Pendimethalin for Control of Phalaris minor in Wheat Crop - S. S. Manhas (Indian Journal of Extension Education, 2017)
The present study was carried out in Barnala district of Punjab during Rabi-2015-16. Front line demonstrations on pendimethalin for control of Phalaris minor in wheat crop were carried out in different farmers’ fields. On comparison with farmers’ practices, it was recorded that the application of pendimethalin @ 1000 ml/acre resulted less Phalaris minor density, weed dry weight and maximum WCE as compared to other farmers practices viz. Clodinafop @160 to 300 g/acre, Pinoxaden 400 to 500 ml/acre, Sulfosulfuron @ 13 g/acre, Mesosulfuron + Iodosulfuron (Atlantis) @160 to 200 g/acre and Sulfosulfuron + Metsulfuron (Total) @ 16g/acre. Application of pendimethalin @ 1000 ml/acre also result more plant height, effective tillers, grain yield, net return and B: C ratio as compared other farmers practices. The application of pendimethalin @ 1000 ml/acre in wheat crop had no residual effect on growth and yield of succeeding crop (fodder maize, sesbania, rice, moong and cotton) as responded by 85 farmers. Lack of knowledge about pendimethalin for weed control in wheat (18.8%), fear of low benefit: cost ratio (16.5%), busy schedule at the time of sowing (14.1%), lack of guidance for pendimethalin application (11.8%), fear of ineffectiveness of pendimethalin (10.6%) were the major reasons towards non-adoption. Publicising the details in respect to dose, time and method of application and intensive training programme on herbicide use in farmers’ field were felt as some crucial steps for increasing the adoption level.